Cognitive Biases in Decision-Making: A Psychological Perspective on Business Excellence - Dewangan , Danesh Kumar (International Journal of Rehabilitation and Special Education (IJRSE), 2025)
Cognitive biases significantly influence decision-making in the business world, often leading to irrational choices that impact organizational success. This paper explores the role of cognitive biases in business decision-making and their implications for achieving business excellence. It categorizes key biases, such as confirmation bias, anchoring bias, and loss aversion, and examines their effects on leadership, strategy, and organizational behavior. Additionally, it discusses methods to mitigate these biases through evidence based decision-making and psychological interventions. Understanding and managing cognitive biases can enhance business performance, foster innovation, and drive sustainable success.
Keywords: Cognitive biases; decision-making; business psychology; leadership; confirmation bias; anchoring bias; loss aversion; behavioral economics; risk assessment; business excellence